Analysis of the Influence of Poverty Rates, Open Unemployment Rates, Economic Growth and District Minimum Wages on Human Development Index in the Province of West Java in 2016-2020 - Indriani, Luky; Arif, Muhammad (Prosiding University Research Colloquium, 2022)
The purpose of this study was to determine the direction and magnitude of the influence of poverty levels, open unemployment rates, economic growth and district minimum wages on the Human Development Index (IPM) in West Java Province in 2016-2020. This research is a quantitative tool used is panel data regression analysis with the selected model FEM (Fixed Effect Model). Based on the results of panel data regression, a it is explained that the Poverty Level has a negative effect on the Human Development Index, the Regency Minimum Wage has a positive effect on the Human Development Index, while Economic Growth and the Open Unemployment Rate have no effect on the Human Development Index in West Java Province.